The subject body, interconnections between landscape, assemblage and the street — a methodological exercise (PerCursos, 2021)
Merleau-Ponty's (2006) conception of body-subject/phenomenal indicates the active existence of the body before the world. This text addresses the relation body-subject with the landscape constituted by the position of the body-space (horizon of thought). The production of a methodology that mobilizes the body in the comprehension of spatial perceptions in the daily experience of the street, through field work, is another propedeutic aspect of this essay. Hence, three theoretical and practical exercises were produced from the position of the body-researcher-space. These exercises are presented in the text in the form of narratives and contemplate the body crossed by the consciousness of reality, imaginary, and space - mediated by the 'thought-landscape'. The articulation of these reflections with discussions about assemblage refers to a perspective of approaching fluid and ephemeral phenomena in Geography.
Keywords: Body; Space; Landscape; Position; Phenomenology